Local and global pyrogeographic evidence that indigenous fire management creates pyrodiversity. Issue 9 (14th April 2015) - Trauernicht, Clay; Brook, Barry W.; Murphy, Brett P.; Williamson, Grant J.; Bowman, David M. J. S.
Abstract: Despite the challenges wildland fire poses to contemporary resource management, many fire‐prone ecosystems have adapted over centuries to millennia to intentional landscape burning by people to maintain resources. We combine fieldwork, modeling, and a literature survey to examine the extent and mechanism by which anthropogenic burning alters the spatial grain of habitat mosaics in fire‐prone ecosystems. We survey the distribution of Callitris intratropica, a conifer requiring long fire‐free intervals for establishment, as an indicator of long‐unburned habitat availability under Aboriginal burning in the savannas of Arnhem Land. We then use cellular automata to simulate the effects of burning identical proportions of the landscape under different fire sizes on the emergent patterns of habitat heterogeneity. Finally, we examine the global extent of intentional burning and diversity of objectives using the scientific literature. The current distribution of Callitris across multiple field sites suggested long‐unburnt patches are common and occur at fine scales (<0.5 ha), while modeling revealed smaller, patchy disturbances maximize patch age diversity, creating a favorable habitat matrix for Callitris . The literature search provided evidence for intentional landscape burning across multiple ecosystems on six continents, with the number of identified objectives ranging from two to thirteen per study. The fieldwork and modeling results imply that the occurrence of long‐unburnt habitat in fire‐prone ecosystems may be an emergent property of patch scaling under fire regimes dominated by smaller fires. These findings provide a model for understanding how anthropogenic burning alters spatial and temporal aspects of habitat heterogeneity, which, as the literature survey strongly suggests, warrant consideration across a diversity of geographies and cultures. Our results clarify how traditional fire management shapes fire‐prone ecosystems, which despite diverse objectives, has allowed human societies to cope with fire as a recurrent disturbance. Abstract : People have intentionally manipulated fire both to alter resource availability and cope with fire as a recurrent threat for centuries to millennia on most continents, yet the effects of these practices on pyrodiversity – ecological heterogeneity wrought by fire – have been difficult to elucidate. We draw on field data from Aboriginal estates and a stochastic simulation to illustrate how spatial patterns in human‐mediated disturbance affect both the spatial and temporal outcomes of habitat heterogeneity. We then use a literature survey to consider the global extent of the practice and how the potential outcomes of patch burning illustrated by the simulation are ultimately driven by a diverse array of objectives, suggesting that human coexistence with fire is closely tied to landscape management.